Small-scale magnetic actuators with optimal six degrees-of-freedom - Xu, Changyu (2022)
Magnetic miniature robots (MMRs) are small-scale, untethered actuators which can be controlled by magnetic fields. As these actuators can non-invasively access highly confined and enclosed spaces; they have great potential to revolutionize numerous applications in robotics, materials science, and biomedicine. While the creation of MMRs with six-degrees-of-freedom (six-DOF) represents a major advancement for this class of actuators, these robots are not widely adopted due to two critical limitations: i) under precise orientation control, these MMRs have slow sixth-DOF angular velocities (4 degree s-1 ) and it is difficult to apply desired magnetic forces on them; ii) such MMRs cannot perform soft-bodied functionalities. Here a fabrication method that can magnetize optimal MMRs to produce 51-297-fold larger sixth-DOF torque than existing small-scale, magnetic actuators is introduced. A universal actuation method that is applicable for rigid and soft MMRs with six-DOF is also proposed. Under precise orientation control, the optimal MMRs can execute full six-DOF motions reliably and achieve sixth-DOF angular velocities of 173 degree s-1 . The soft MMRs can display unprecedented functionalities; the six-DOF jellyfish-like robot can swim across barriers impassable by existing similar devices and the six-DOF gripper is 20-folds quicker than its five-DOF predecessor in completing a complicated, small-scale assembly.